PERANCANGAN DAN PENGEMBANGAN ALAT UJI TARIK MINI BERBASIS ARDUINO UNTUK SPESIMEN NON-FERRO - Comaro, Julham; Malik, Irawan; ., Karmin (Politeknik Negeri Sriwijaya, Indonesia, 2020)
Tensile test mechine is one of the most important research and educational means in supporting and supporting the learning process of teaching in the laboratory used to know the mechanical properties of materials. Currently commercial tensile testing tools are very accurately used in measuring mechanical properties, but cost and size make it impractical for classroom direct learning. This research and development experimented to design and create a small capacity tensile testing tool capable of producing tools that are more efficient, economical, and have high anemicity by utilizing the available hardware and software while keeping an eye on and maintaining the quality of the production results. This Tensile test tool uses nema 17 stepper motor as drive motor, to transmit power using 2 ballscrew, belt, and pulley. Load cell and digimatic sensors are used for reading the magnitude and extension of specimens controlled by the Arduino microcontroller.Â Keywords: Tensile Test, Ioad Cell, Voltage, StrainBlank